Follistatin-like protein 1 regulates chondrocyte proliferation and chondrogenic differentiation of mesenchymal stem cells. Issue 7 (18th March 2014) - Chaly, Yury; Blair, Harry C; Smith, Sonja M; Bushnell, Daniel S; Marinov, Anthony D; Campfield, Brian T; Hirsch, Raphael
Abstract : Objectives: Chondrocytes, the only cells in the articular cartilage, play a pivotal role in osteoarthritis (OA) because they are responsible for maintenance of the extracellular matrix (ECM). Follistatin-like protein 1 (FSTL1) is a secreted protein found in mesenchymal stem cells (MSCs) and cartilage but whose function is unclear. FSTL1 has been shown to modify cell growth and survival. In this work, we sought to determine whether FSTL1 could regulate chondrogenesis and chondrogenic differentiation of MSCs. Methods: To study the role of FSTL1 in chondrogenesis, we used FSTL1 knockout (KO) mice generated in our laboratory. Proliferative capacity of MSCs, obtained from skulls of E18.5 embryos, was analysed by flow cytometry. Chondrogenic differentiation of MSCs was carried out in a pellet culture system. Gene expression differences were assessed by microarray analysis and real-time PCR. Phosphorylation of Smad3, p38 MAPK and Akt was analysed by western blotting. Results: The homozygous FSTL1 KO embryos showed extensive skeletal defects and decreased cellularity in the vertebral cartilage. Cell proliferation of FSTL1-deficient MSCs was reduced. Gene expression analysis in FSTL1 KO MSCs revealed dysregulation of multiple genes important for chondrogenesis. Production of ECM proteoglycans and collagen II expression were decreased in FSTL1-deficient MSCs differentiated into chondrocytes. Transforming growth factor β signalling in FSTL1 KO cells was significantly suppressed. Conclusions: FSTL1 is a potent regulator of chondrocyte proliferation, differentiation and expression of ECM molecules. Our findings may lead to the development of novel strategies for cartilage repair and provide new disease-modifying treatments for OA.